AP2/ERF Transcription Factor, Ii049, Positively Regulates Lignan Biosynthesis in Isatis indigotica through Activating Salicylic Acid Signaling and Lignan/Lignin Pathway Genes - Ma, Ruifang; Xiao, Ying; Lv, Zongyou; Tan, Hexin; Chen, Ruibing; Li, Qing; Chen, Junfeng; Wang, Yun; Yin, Jun; Zhang, Lei; Chen, Wansheng (Frontiers in Plant Science, 2017)
Lignans, such as lariciresinol and its derivatives, have been identified as effective antiviral ingredients in Isatis indigotica. Evidence suggests that the APETALA2/ethylene response factor (AP2/ERF) family might be related to the biosynthesis of lignans in I. indigotica. However, the special role played by the AP2/ERF family in the metabolism and its underlying putative mechanism still need to be elucidated. One novel AP2/ERF gene, named Ii049, was isolated and characterized from I. indigotica in this study. The quantitative real-time PCR analysis revealed that Ii049 was expressed highest in the root and responded to methyl jasmonate, salicylic acid (SA) and abscisic acid treatments to various degrees. Subcellular localization analysis indicated that Ii049 protein was localized in the nucleus. Knocking-down the expression of Ii049 caused a remarkable reduction of lignan/lignin contents and transcript levels of genes involved in the lignan/lignin biosynthetic pathway. Ii049 bound to the coupled element 1, RAV1AAT and CRTAREHVCBF2 motifs of genes IiPAL and IiCCR, the key structural genes in the lignan/lignin pathway. Furthermore, Ii049 was also essential for SA biosynthesis, and SA induced lignan accumulation in I. indigotica. Notably, the transgenic I. indigotica hairy roots overexpressing Ii049 showed high expression levels of lignan/lignin biosynthetic genes and SA content, resulting in significant accumulation of lignan/lignin. The best-engineered line (OVX049-10) produced 425.60 μg·g-1 lariciresinol, an 8.3-fold increase compared with the wild type production. This study revealed the function of Ii049 in regulating lignan/lignin biosynthesis, which had the potential to increase the content of valuable lignan/lignin in economically significant medicinal plants.